The Alternative Binary Geothermal Power-Plant Design to Utilize the Waste Heat in Lahendong Plant - Eli Kumolosari; Bahrul Jalaali; Kutut Suryopratomo; Okto Dinaryanto (Institut Teknologi Dirgantara Adisutjipto, 2020)
The first geothermal binary system in Indonesia that has successfully implemented is a 500kW binary system in Lahendong. Yet, there is still a plenty room of improvement for binary system development in Lahendong. This study aims to give an alternative design of the binary system by using an organic Rankine cycle. The investigations of thermodynamic analysis based on the law of thermodynamics, silica scaling analysis, and optimization of working fluid selection are presented. Flashing process from separator produces vapor and liquid-brine with mass flow rates 48.6 kg/s and 173.6 kg/s at separator pressure of 10.23 bar. Based on second law thermodynamics analysis, obtained the maximum useful energy from brine flow is 7.2MW. Based on the simulation results, it is achieved that the potential power generated by waste heat from the Lahendong plant is 2.46MW with the net thermal and exergy efficiency by 11% and 34%, respectively. Compared to the current operating binary system, still, much available energy needs to be harnessed in the future from the Lahendong plant.